HYBRID+ISM 2007 : Sabah Art Gallery - Universiti Malaysia Sarawak, Faculty of Applied and Creative Arts (Universiti Malaysia Sarawak (UNIMAS), 2007)
Hybrid+ism 2007 is one of the many activities that the faculty has in line for the year 2007. "Ihe theme 'Hybrid+ism' was chosen as it is very much in line with the faculty's efforts to showcase art exhibitions portraying the integration of arts with various media in tandem with current global developments where art is a form of knowledge. I hope this exhibition will provide an opportunity for all to meet, share insights and exchange new knowledge and experiences as well as create a place to deliberate on promoting and enhancing the development of the arts.